ANALYSIS OF HAJJ FINANCING IN BANK PANIN DUBAI SYARIAH - Aisyah, Esy Nur; Febrian, Junanda (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Muslims who are able to physically and materially visit Allah's house must perform the hajj, a form of worship that is one of the pillars of Islam. This research uses qualitative methods. The purpose of this research is to analyze the Hajj financing products offered by Bank Panin Dubai Syariah. The Hajj financing product (Prohajj) at Bank Panin Dubai Syariah Malang is a bridging loan to customers to cover the lack of funds to obtain a Hajj. The DSN-MUI Fatwa Number 29/DSN-MUI/VI/2002, which pertains to Financing for Hajj Management by Sharia Financial Institutions, allows Sharia Financial Institutions to offer Hajj bailout products or Hajj financing. We hope that this fatwa will encourage all Islamic financial institutions to adhere to the established regulations